Estimation of percentile residual life function with left-truncated and right-censored data. Issue 2 (17th January 2017) - Zhao, Mu; Jiang, Hongmei; Zhou, Yong
ABSTRACT: This article focuses on the estimation of percentile residual life function with left-truncated and right-censored data. Asymptotic normality and a pointwise confidence interval that does not require estimating the unknown underlying distribution function of the proposed empirical estimator are obtained. Some simulation studies and a real data example are used to illustrate our results.